PARTISIPASI PEMILIK RUMAH KOS DALAM IMPLEMENTASI PERDA KOTA SEMARANG NO. 3 TAHUN 2011 DI KELURAHAN TEMBALANG - Prastiwi, Mey; Yuniningsih, Tri (Journal of Public Policy and Management Review, 2017)
Participation is a manifestation of the awareness, caring, and responsibility of the community towards the development. Tembalang district is the center of educational development in Semarang City, it is causing the increase of the number of newcomers every year has an impact on the number of problems that arise in Tembalang sub district, one of them is the taxes for boarding house with more than 10 rooms, which is charged up to 10% tax. The purpose of this study was to describe and analyze the community participation of boarding house holders on 2001, number 3 of regional regulation implementations in Semarang, in Tembalang district, And to identify what are the factors inhibiting the low of community participation of householders on 2001, number 3 of regional regulation implementations in Semarang, Tembalang district. This research using descriptive type with qualitative approach. Data collection techniques used are interview and documentation. The results of this study indicate that the form of the participation of boarding house holders still in the form of participation of all tau psudeo participation, while the level of participation are nonparticipation level. The internal factors that influencing the low level of participation are certain culture trust, while the external factor is stakeholderss.